Torchwood. Miracle day [videorecording (DVD)] - Barrowman, John, 1967-; Myles, Eve, 1978-; Phifer, Mekhi, 1975-; Havins, Alexa; Owen, Kai, 1975-; Pullman, Bill (BBC, 2012)
When convicted child killer Oswald Danes miraculously survives his own execution, the footage holds America transfixed. And then everyone realizes that nobody is dying. All across the world, nobody dies. And then the next day, and the next, and the next. People keep aging, they get hurt and sick, but they never die.